Pengaruh Kualitas Pelayanan Dan Manajemen Hubungan Pelanggan Terhadap Kepuasan Pelanggan Pada Perumda Tirta Patriot Kota Bekasi - Karlina Eris; Mercy Spesa Devina De Fretes (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Customer satisfaction has a strategic role because it is directly related to social responsibility and thequality of life of the community who rely on clean water supplies every day. This study aims to analyzethe effect of service quality and customer relationship management, both partially and simultaneously,on customer satisfaction at Perumda Tirta Patriot Bekasi City. Using a quantitative approach, the numberof samples in this study was 150 customers. Data were analyzed through multiple regression analysis,ttest, F-test and coefficient of determination test. The results of the study indicate that service qualityhas a positive and significant effect on customer satisfaction as indicated by the calculated t value (7.559)> t table (1.976), customer relationship management has a positive and significant effect on customersatisfaction as indicated by the calculated t value (8.163) > t table (1.976) and simultaneously the twoindependent variables have a positive and significant effect on customer satisfaction as indicated by thecalculated F value (316.552) with a significance value of 0.000. These results indicate that the twovariables have an important role in increasing customer satisfaction by 81.2%, while the rest is influencedby other factors not studied.Keywords: Service Quality, Customer Relationship, Management , Customer Satisfaction